Beta-blockers in modern glaucoma therapy. Review - O. A. Kiseleva; L. V. Yakubova; A. M. Bessmertny (Oftalʹmologiâ, 2014)
Provides information about the beta-blockers: history, mechanism of action, adverse systemic and local effects, the use in the treatment of glaucoma and ocular basic forms used in Russia.